Development and validation of a counselor therapeutic-relationship value scale - Dizon, Edilberto I. (1982)
The objective of the study is to develop a counselor therapeutic-relationship value scale consisting of three facilitative dimensions: empathic understanding, congruence, and unconditional positive regard. This study also evaluates the counselor therapeutic-relationship through item and scale validation procedures. This aims to determine the differences between/among the respondents, grouped according to each of ten variables: region, sex, age, civil status, type of school, educational attainment, length of counseling experience, level of counseling work, length of simultaneous teaching and counseling experience. It is anticipated that the scale will be of value in counselor self-awareness, development, and training, and in research.
Thesis (Ed.D.)--University of the Philippines, Quezon City.
Keywords: Values -- Testing